Removal of Colour (Direct Blue 199) from Carpet Industry Wastewater Using Different Biosorbents (Maize Cob, Citrus Peel and Rice Husk) - Saroj S.; Singh S.V.; Mohan D. (My University, 2025)
Direct Blue 199 is used to colour carpets. In this study, adsorbents prepared from maize cob, citrus peel and rice husk (agricultural wastes) were used to study removal of Direct Blue 199 from its aqueous solution and a carpet industry’s effluent. The adsorption equilibrium studies were carried out by varying the adsorbent dosage at a constant temperature of (Formula presented.). Adsorption of the dye varied with different adsorbents. Equilibrium adsorption data were correlated using Langmuir isotherms for all the three adsorbents. Kinetic study showed that it took about 2 h for 80–90% removal. Kinetic data for all the systems studied could be correlated satisfactorily by pseudo-second-order rate equation. It is confirmed by statistical t test (paired two samples for means) that the predicted and observed data were not significantly different statistically. The studies indicated that the adsorbents, maize cob, citrus peel and rice husk powders can be used as low-cost alternatives for the dye removal. © 2015, King Fahd University of Petroleum & Minerals.